Optimasi Pengaturan Parameter Bubut pada Material SKD 11 terhadap Kekasaran dan Material Removal Rate Menggunakan Metode Taguchi Grey Fuzzy - Anita Nuryanti; Pranowo Sidi; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Within the increasing of competitive and demand for quality product in the market place, therefore the demands for quality for metal cutting are getting higher, one of them are turning process. The quality of the product can be seen from the surface roughness and material removal rate. Surface rougness have a affect in functional product. The more smaller in roughness, the quality is more better. Material removal rate in the machining process is very important because it relates to dimensional accuracy in tool, dies serta mold. This research using parameter related to turning such as spindle speed, feed rate and depth of cut for material SKD 11 using chisel CNMG. The analysis was performed using Taguchi Grey Fuzzy methd by combining two responses of surface roughness and material removal rate. The result shows that, feed rate, spindle speed and depth of cut has no significant effect to surface roughness and material removal rate. The percent contribuion od feed rate 0,086% depth of cut 15,44% and spindle speed 5,216%. The optimum combination of parameters